Factors that influence saving behaviour in Malaysia / Muhamad Azamuddin Muhamad Farid and Izzati Diyana Ihsan - Muhamad Farid, Muhamad Azamuddin; Ihsan, Izzati Diyana (Faculty of Business and Management, 2014)
This paper aims at determining the determinants of saving behaviour in Malaysia. The variables are interest rate, inflation, consumption, income level, quantitative easing and rate of return. The sample of this study comprises of 30 observations each of the independent and dependent variables on a monthly basis for 30 years period from January 1983 to December 2013. Methodology used for this study is by using Multiple Linear Regression with time series data sourced from Department of Statistics, Ministry of Finance, and World Bank data. Therefore, econometric tests are to be conducted to know the determinants of variable such as interest rate, inflation rate, income level, consumption, quantitative easing and rate of return towards saving behaviour in Malaysia. Interactive software package E-view would be used for testing and analysing the data collected. The study is an attempt to investigate the determinants of saving behaviour in Malaysia. The results of this research paper would provide us with an indicative view and could form an important basis for investors and policy makers in their investment strategies and policy decisions respectively.